Evaluation of Resource Optimization and Program Project Management in the ICT Industry using COBIT 5.0 - Romersono, Jansi Kamasi Ramantha; Oetama, Raymond (AI Society & STMIK Indonesia, 2023)
Practical Information Technology Governance will establish efficiency alongside high-quality service within a corporate organization. Its execution must be meticulously strategized to ensure optimal implementation. Nonetheless, internal and external assessments are also imperative. These evaluations are intended to rectify prevailing issues in Information Technology Governance within the organization, enabling the Company's IT systems to function at their peak. Consequently, the necessity for IT Governance is paramount. The research methodology to be employed will make use of the COBIT 5 framework formulated by ISACA. The research objective is to appraise the competence of Information Technology Governance within the organization. The research process will encompass interviews with a representative from the organization, particularly the Human Resource Development supervisor. It facilitates the organization in more readily adhering to the measures recommended by auditors to address any hindrances that may be present in their IT Governance.